2019
DOI: 10.1111/hiv.12751
|View full text |Cite
|
Sign up to set email alerts
|

Increased monocyte activation with age among HIV‐infected long term non‐progressor children: implications for early treatment initiation

Abstract: Objectives The key to newer therapeutic and eradication approaches often lies in understanding slow disease progression in HIV infection. The paediatric population has been poorly studied in this regard. We aimed to describe a cohort of perinatally infected long‐term nonprogressor (LTNP) children living with HIV in India and to evaluate the immune biomarkers of disease progression. Methods LTNPs (ART‐naïve, with a CD4 count ≥ 500 cells/μL at age ≥ 7 years) among the cohort of HIV‐infected children were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Several studies showed that increased monocyte turnover better predicts the tempo of progression to AIDS in HIV-infected patients and SIV/SHIV-infected animals than declining level of CD4 + T cells alone [33,34]. Although CD4 + T cells are the major source of virus production in HIV-infected individuals, monocytes/macrophages contribute substantially to plasma viral load during late-stage of HIV disease when the levels of circulating CD4 + T cell are very low [35], even is associated with the gradual loss of nonprogressor status in the long-term nonprogressors (LTNPs) [36]. Our previous study showed that SHIV KU−1 -infected Chines RMs had the persistence of high virus loads (10 6 -10 8 viral RNA copies per ml) with a 1.5 years survival time, although their circulating CD4 + T cell levels were very low (10-250 cells/ul) over the course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that increased monocyte turnover better predicts the tempo of progression to AIDS in HIV-infected patients and SIV/SHIV-infected animals than declining level of CD4 + T cells alone [33,34]. Although CD4 + T cells are the major source of virus production in HIV-infected individuals, monocytes/macrophages contribute substantially to plasma viral load during late-stage of HIV disease when the levels of circulating CD4 + T cell are very low [35], even is associated with the gradual loss of nonprogressor status in the long-term nonprogressors (LTNPs) [36]. Our previous study showed that SHIV KU−1 -infected Chines RMs had the persistence of high virus loads (10 6 -10 8 viral RNA copies per ml) with a 1.5 years survival time, although their circulating CD4 + T cell levels were very low (10-250 cells/ul) over the course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that increased monocyte turnover better predicts the tempo of progression to AIDS in HIV-infected patients and SIV/SHIV-infected animals than declining level of CD4 + T cells alone [33,34]. Although CD4 + T cells are the major source of virus production in HIV-infected individuals, monocytes/macrophages contribute substantially to plasma viral load during late-stage of HIV disease when the levels of circulating CD4 + T cell are very low [35], even is associated with the gradual loss of nonprogressor status in the long-term nonprogressors (LTNPs) [36]. Our previous study showed that SHIV KU−1 -infected Chines RMs had the persistence of high virus loads (10 6 -10 8 viral RNA copies per ml) with a 1.5 years survival time, although their circulating CD4 + T cell levels were very low (10-250 cells/ul) over the course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, 82% (64–98%) of pregnant or breast feeding people living with HIV had access to antiretroviral therapy (ART), meaning 220,000 pregnant women could not access ART for themselves or to prevent transmission to their infants [ 2 , 3 ]. Without treatment, 50% of infants will die before their second birthday, although up to 10% will survive into adolescence, with minimal symptoms, reflecting the diverse disease progression of paediatric HIV [ 4 ]. AIDS-related deaths peaked in children in 2004 at 360,000 and whilst deaths fell by 64% from 2010 to 84,000 in 2022, this represented 13% of global AIDS-related deaths, yet children make up just 4% of people living with HIV [ 3 ].…”
Section: Introduction and Epidemiologymentioning
confidence: 99%